HUBUNGAN ANTARA DESAIN KURSI KERJA DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA PEKERJA BAGIAN PENENUNAN DI CV. PIRSA ART PEKALONGAN - Astutik, Sri (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Low Back Pain is a gripe that often happens to worker with prevalence reaches 31,6%. The aim of this study is to find out the correlation between height of chair, length of the base of chair, width of the base of chair desaign of working chair and low back pain gripe on weave worker of CV. Pirsa Art Pekalongan. This study is explanary research with cross sectional approachment. The population of this study all the weave worker of CV. Pirsa Art Pekalongan as many as 20 people. Sample of this study is all the weave worker of CV. Pirsa art Pekalongan as many as 20 people (using total sampling technique). The instrument that used in this study is rolled and assessment sheet. The analysist of data is conducted univariat and bivariat (using chi-square test with α=0,05). The result of this study, variable which related with low back pain on weave worker of CV. Pirsa art Pekalongan is the height of chair (ρ=0,02) and the length of the base of chair (ρ=0,015). According to the result of study, there is a correlation between the height of chair and the length of the base of chair with low back pain gripe. Suggestion which given to the worker is that the worker should pay attention to their resting time also doing warming up before working. For the owner of weaving factory is suggested to supply chair that fulfill the criteria of ergonomics chair size appropriate with anthropometry of the worker.